Efisiensi Pemerataan Kebiajakan Moeneter Dalam Persepektif Syariah Dan Pengaruhnya Terhadap Tingkat Inflasi Di Indonesia - Radiansyah, M.; Munawaroh, Munawaroh; Fahmi D, Aswin; Harahap, M. Guffar (Al-Sharf: Jurnal Ekonomi Islam, 2023)
Indonesia is one of the developing countries trying to face the obstacles for which monetary policy is present to see and measure how effective it is in affecting Indonesian inflation rates. Indonesia, as the country with the largest Muslim population, has begun to implement Islamic values in economic activities, including monetary policy. The aim of this study is to see to what extent the level of monetary policy efficiency from Islamic perspectives and its impact on inflation rates in Indonesia The method used in this research is a library research method, and the data used is secondary data that corresponds to the relevant literature. Looking at the level of policy efficiency through Islamic perspectives and its influence on inflation rates shows that it has not yet reached an efficient point in controlling inflation levels, but Islamic policy coverage has a large scope.